Correlation of Prenatal and Postnatal MRI Findings in Schizencephaly - Nabavizadeh, S.A. (AJNR Am J Neuroradiol, 2014)
BACKGROUND AND PURPOSE: Schizencephaly is a rare malformation of the brain characterized by a gray matter–lined defect extending from the pial surface to the lateral ventricles. The purpose of this study was to correlate imaging findings of schizencephaly and associated anomalies on fetal and postnatal MR imaging and assess possible changes that may occur from the prenatal-to-postnatal state. MATERIALS AND METHODS: A retrospective review of subjects with schizencephaly who had both pre- and postnatal MR imaging was performed. Subject age, cleft type, number, location, and features of the defects and associated anomalies were recorded. Normalized dimensions of the defect and ipsilateral ventricle were measured and correlated to changes in the clefts between pre- and postnatal imaging. RESULTS: Ten subjects with 18 clefts (8 bilateral) were included. Most defects (83%) were open on prenatal MR imaging, but 47% of those were found to have subsequently closed on postnatal imaging. Evidence of prior hemorrhage was seen in 83%. Prenatal MR imaging detected all cases of an absent septum pellucidum but detected a fraction of gross polymicrogyria and missed all cases of optic nerve hypoplasia. The normalized ipsilateral ventricular and inner and middle width dimensions of the defects were significantly decreased at postnatal imaging (P < .05). The widths of the defects, ventricular width, and presence of hemorrhage were not predictors of closure of prenatally diagnosed open defects (P > .05). CONCLUSIONS: In our series, nearly half of prenatally open schizencephaly defects had closed on postnatal imaging. Prenatal MR imaging was only able to demonstrate some of the associated anomalies.